Entrepreneurial strategic management - Blawatt, Ken R. (2014 digital library., 2014)
A managerial book that goes beyond the verge of traditional texts on the subject. It brings to management a challenging dimension: Create an entrepreneurial organization and you will exceed in the realization of your goals and objectives. The entrepreneurial organization thrives on developing innovation, customer retention, productivity, and growth. The role of management has changed dramatically in the last decade with the joining of powerful new forces in the environment. A new social awareness and demographic shift in the workforce coupled with a shrinking of markets in a technological and global landscape demands new ways of planning, organizing, and directing organizations. ESM argues the need for implementation as the force majeure in fulfilling strategic plans and the engagement of the whole organization in strategic management to achieve organizational goals.